THE INFLUENCE OF NITROGEN FERTILIZERS ON SOYBEAN YIELDS AND SEED QUALITY - Liashenko, V.V.; Lotysh, I.I.; Taranenko, A. O.; Krykunova, V.Yu.; Kundyus, K. O. (Scientific Progress & Innovations, 2019)
The study of combining phosphorus-potassium fertilizers and nitrogen (N) fertilizers in fertilization sys-tem, which is necessary for soybean genetic potential realization, was presented in the research. It has been determined that the main factor influencing the genetic potential realization of soybean productivity is apply-ing N fertilizers, which also reduces moisture consumption for the formation of soybean yield unit. It was proved that applying 60 and 90 kg ha-1 of N against the background of 60 kg ha-1 of P and 60 kg ha-1 of K enabled to reduce moisture consumption by 34–39% for the formation of yield unit as compared without N fertilization variant. The increase of nitrate and ammonium nitrogen content in soil layers from 0 to 20 cm by 1.1 % and from 20 to 40 cm by 4.7 % at applying 30 and 90 kg ha-1 N against the background of 60 kg ha-1 of P and 60 kg ha-1 of K was shown. According to the research results positive effect of N fertiliz-ers on biometric indexes of soybean plants was revealed. Increasing N fertilization rates contributed to im-proving the quality of plant indexes. The best results were shown in the variants with nitrogen fertilization against phosphorus-potassium background. The increase of N fertilization rates led to improving the rele-vant indicators. It has been established that the highest average soybean yield was observed in the variant of applying 90 kg ha-1 N – 253 kg ha-1, as compared with the variant without N fertilization – 73 kg ha-1. The difference between soybean yield in the variants of applying 30 and 60 kg ha-1 of N was 16 kg/ha. The posi-tive impact of N fertilization on the quality of soybean seed was proved. During our experiment, the maxi-mum protein content in soybean seeds (38.2 %) and highest yield – 97 kg/ha were obtained in the variant of applying 90 kg ha-1. The maximum grain fat content was found in the variant without N fertilization – 22.0 %. N fertilization improved the conditions of mineral nutrition and reduced grain fat content to 20.1 %. According to the research results we recommend N fertilization against phosphorus-potassium background to obtain high soybean yields.